Germany's debt brake: Pulling the EU out of its debt trap? - Ognian N. Hishow (Intereconomics, 2011)
How high would be the opportunity costs of the introduction of a German-style debt brake in other EU member states? The following article calculates these and concludes that they would in many cases be politically unacceptable. The author proposes an alternative solution, a 'debt brake light'.
Keywords: 330